A Knitted PET Patch Enhances the Maturation of Regenerated Tendons in Bridging Reconstruction of Massive Rotator Cuff Tears in a Rabbit Model. Issue 4 (March 2023) - Zhong, Yuting; Jin, Wenhe; Gao, Han; Sun, Luyi; Wang, Peng; Zhang, Jian; Ong, Michael Tim Yun; Sai Chuen Bruma, Fu; Chen, Shiyi; Chen, Jun
Background: Although nondegradable synthetic grafts for bridging reconstruction of massive rotator cuff tears (MRCTs) have shown satisfactory clinical outcomes, their function and details on graft-tendon healing and enthesis regeneration have not been fully studied. Hypothesis: The knitted polyethylene terephthalate (PET) patch as a nondegradable synthetic graft could provide sustained mechanical support, facilitating enthesis and tendon regeneration in the treatment of MRCTs. Study Design: Controlled laboratory study. Methods: A knitted PET patch was fabricated for bridging reconstruction (PET group) in a New Zealand White rabbit model of MRCTs (negative control group), and an autologous Achilles tendon was used as a control (autograft group). The animals were sacrificed, and tissue samples were harvested for gross observation as well as histological and biomechanical analyses at 4, 8, and 12 weeks postoperatively. Results: Histological analysis showed no significant difference in the graft-bone interface score between the PET and autograft groups at 4, 8, and 12 weeks postoperatively. Interestingly, in the PET group, Sharpey-like fibers were observed at 8 weeks, while fibrocartilage formation and the ingrowth of chondrocytes were recognized at 12 weeks. Meanwhile, the tendon maturing score was significantly higher in the PET group than in the autograft group (19.7 ± 1.5 vs 15.3 ± 1.2, respectively; P = .008) at 12 weeks, with parallel-oriented collagen fibers around the knitted PET patch. Moreover, the ultimate failure load of the PET group was similar to that of a healthy rabbit tendon at 8 weeks (125.6 ± 13.6 vs 130.8 ± 28.6 N, respectively; P > .05) and no different from that of the autograft group at 4, 8, and 12 weeks. Conclusion: The knitted PET patch could not only immediately reconstruct the mechanical support for the torn tendon postoperatively in the rabbit model of MRCTs but also enhanced maturation of the regenerated tendon by fibrocartilage formation and improved the organization of collagen fibers. Herein, the knitted PET patch could be a promising candidate graft adopted in bridging reconstruction of MRCTs. Clinical Relevance: A nondegradable knitted PET patch can safely bridge MRCTs with satisfactory mechanical strength and the promotion of tissue regeneration.